# Thread: Simplify each expression as far as possible...

1. ## Simplify each expression as far as possible...

I am having trouble with these problems, I was told to practice this for my next quiz that I am going to have but on our crunch course (5 week) the guy doesen't explain anything and so I really don't get it.

Can someone help me out?

I am suppose to Simplify each expression as far as possible. Write my answer using positive exponents only. (I usually use 3 to verify my answer)

Thanks

2. Originally Posted by elitescouter

I am having trouble with these problems, I was told to practice this for my next quiz that I am going to have but on our crunch course (5 week) the guy doesen't explain anything and so I really don't get it.

Can someone help me out?

I am suppose to Simplify each expression as far as possible. Write my answer using positive exponents only. (I usually use 3 to verify my answer)

Thanks
1. $(3x)^{-3}$
= $\frac{1}{(3x)^3}$
= $\frac{1}{3^3 x^3}$
= $\frac{1}{27 x^3}$

again 1st
1. $(3x)^{-3}$
= $3^{-3}x^{-3}$
= $\frac{1}{27}\frac{1}{x^3}$

7. $3x^{-2}(x^8+2x^2)$+ $2(x^3)^2$
= $3x^{-2}.x^8+3x^{-2}.2x^2+2.(x^3)^2$
............... $(x^a)^b=x^{ab}$
............... $x^a.x^b=x^{a+b}$
= $3x^6+3.2x^0+2.x^6$
= $3x^6+6+2.x^6$
= $3x^6+2.x^6+6$
= $5x^6+6$

Try others...and tell whether you get them or not...and the above ones as well